THE RELEVANCE OF CIVIC EDUCATION IN NATIONAL CHARACTER BUILDING: A LITERATURE REVIEW - Darmawati. R (Adisam Publisher, 2025)
Civic Education (Civics Education) has an important role in shaping the nation's character. This literature review aims to examine the relevance of Civics Education in shaping the nation's character. The results show that Civics Education acts as a vehicle to develop the values of Pancasila, strengthen the nation's identity, and form citizens who are smart, skilled, and characterised. Civics learning not only provides knowledge about citizenship, but also develops the attitudes and skills needed to become active and responsible citizens. Through Civics, students are expected to integrate character values such as nationalism, patriotism, tolerance, justice, and democracy in their daily lives. However, the effectiveness of Civics in shaping the nation's character is also influenced by various factors, such as curriculum, teacher competence, school and community environment, infrastructure, and learning evaluation. Synergistic and sustainable efforts are needed from various parties to optimise the role of Civics in shaping the nation's character. Thus, Civics can be a strong foundation in building a young generation that has character, loves the country, and is able to face global challenges while remaining grounded in the noble values of the nation.